1998
DOI: 10.1086/516311
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Isolation and Characterization of a Calicivirus Causing a Vesicular Disease of the Hands and Feet

Abstract: We report that a calicivirus of oceanic origin, San Miguel sea lion virus serotype 5 (SMSV-5), is a human pathogen. This biotype was isolated originally from blisters on the flippers of northern fur seals (Callorhinus ursinus) and replicates readily in primate and human cell lines. It infects a phylogenetically diverse array of hosts (poikilotherms to primates) and induces type-specific neutralizing antibodies in exposed humans. Group antibody against a pooled antigen of SMSV-5 and two other serotypes was also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
58
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 2 publications
1
58
0
Order By: Relevance
“…The epidemics of VESV in North America from the 1930s to 1950s were shown by classical virological investigations to be serotypes of marine origin (56,57,65). SMSV was also found in vesicular lesions in humans, and antibodies were detected in blood donors (54,55).…”
mentioning
confidence: 97%
“…The epidemics of VESV in North America from the 1930s to 1950s were shown by classical virological investigations to be serotypes of marine origin (56,57,65). SMSV was also found in vesicular lesions in humans, and antibodies were detected in blood donors (54,55).…”
mentioning
confidence: 97%
“…Recent studies have indicated that some animal caliciviruses are capable of crossing species barriers and potentially use humans as their hosts. One serotype of SMSV was reported to infect humans (51,53). The zoonotic potential of feline calicivirus has been suggested by the observation of a human antibody against it (53).…”
mentioning
confidence: 99%
“…At least 16 serotypes of SMSV have been identified, of which serotypes 1 and 4 have been further characterized (40). One serotype of SMSV has a list of several natural hosts that includes seals, cattle, whales, donkeys, and humans (51). A unique feature of vesiviruses is that the capsid protein present in the mature virion is a cleaved product of the capsid protein precursor encoded by the second ORF (5,15,56).…”
mentioning
confidence: 99%
“…Vesivirus infection has been documented in humans in more occasions and in a multiplicity of clinical outcomes (encephalitis, hepatitis, myocarditis, pneumonia, spontaneous abortion and dermatitis) [10][11][12]. Also, antibodies to marine and terrestrial vesiviruses and vesivirus genome sequences have been detected in blood donors in the United States [13].…”
Section: Introductionmentioning
confidence: 99%